Development of a ptp2-LAMP assay for the specific and sensitive detection of Nosema apis and its comparison with ptp3-LAMP for the detection of Nosema ceranae, in a region endemic for both microsporidium pathogens of the Western honey bee - Lannutti, Lucas; Gisder, Sebastian; Florin-Christensen, Monica; Genersch, Elke; Schnittger, Leonhard (Elsevier, 2025)
The Western honey bee plays a pivotal role in global food security as the primary commercial pollinator. The microsporidian pathogens Nosema apis and Nosema ceranae infect the bee midgut, causing nosemosis, a debilitating infectious disease that results in considerable economic losses in apiculture. Traditionally, Nosema spp. infection is diagnosed by microscopic detection and quantification of spores. However, only molecular diagnostics allow differentiation between N. apis and N. ceranae. Loop-mediated isothermal amplification (LAMP) is a rapid, highly specific, and sensitive DNA detection method. The present study aimed to develop a LAMP protocol for N. apis based on the species-specific single copy polar tube protein 2 (ptp2) gene, and to analyze and compare its diagnostic performance with the previously developed polar tube protein 3 (ptp3) gene-based LAMP protocol for N. ceranae. The ptp2- and ptp3-LAMP assays specifically identified N. apis and N. ceranae, respectively. Their analytical sensitivity was tested using serial dilutions of plasmid and genomic DNA, demonstrating that ptp2- and ptp3-LAMP consistently detected down to 103 ptp2 and 104 ptp3-gene copies, respectively. Amplification was verified by agarose gel electrophoresis (conventional format), and by a change from pink to yellow color after addition of a suitable dye (colorimetric format). The ptp2- and ptp3-LAMP assays and a reference duplex PCR were applied to a panel of field samples (n = 55) from a region endemic for both Nosema spp. Conventional and colorimetric ptp2-LAMP showed an almost perfect test agreement (kappa value > 0.81) compared with duplex PCR. Conventional and colorimetric ptp3-LAMP assays showed a substantial (kappa value > 0.60) and almost perfect test agreement (kappa value > 0.81), respectively. The ptp2- and ptp3-LAMP assays provide excellent performance, ease of implementation, cost savings, and rapid execution, making them ideal choices for molecular detection and differentiation of N. apis and N. ceranae.